A Conceptual Model of Role Based Access Control Using Role Mining Algorithm - Nazirah Abd Hamid; Rabiah Ahmad; Siti Rahayu Selamat (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
Numerous studies have shown that currently, role-based access control has becoming one of the successful access control model because of its principle that could simplifies the work of security administrators. However, to construct a concise, role-based access control system, a good role mining algorithm structure is needed therefore the objectives of this paper are firstly, to provide a general overview on phases that involved in designing and developing the algorithm and secondly, to introduce a conceptual model that constructed based on the analysis and this model represents a general process in role mining model. This model involved series of phases that begin with the input of data, pre-processing stage, candidate role generation phase, role selection and role assignment process and lastly number of roles as generated output.